Implementasi Metode Presentasi dalam Pembelajaran Filsafat Islam di Perguruan Tinggi Islam Swasta - Muzakkih, Ahmad (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
Learning Islamic philosophy can increase students' activeness and understanding in thinking critically. The results of the study concluded that: (1) the application of the presentation method in learning Islamic philosophy at the Hasanuddin Pare Islamic Institute, with several steps in using the presentation method, which includes: (a) planning, in the planning there are several stages, which include: determining the material, objectives achieved, methods used, facilities and infrastructure needed; (b) implementation, in its implementation there are several stages, which include: preparing the place and tools, delivering material, discussing material, Lecturer conclusions; (2) the results of the application of the presentation method in learning Islamic philosophy at the Hasanuddin Pare Islamic Institute, by using the presentation method in learning, which includes: students are required to be more active in learning activities, students carry out several stages to make papers and powerpoints to be presented, students are free to look for various reference materials in books, journals and papers, students understand in detail the material they get in various references, students master the material when presenting and students are very enthusiastic in learning Islamic philosophy using the presentation method, and supported by an LCD projector.